The Concept of the Archipelagic State in Addressing Maritime Security Threats - Yunias Dao; Yusnaldi; Kusuma; Panji Suwarno; Pujo Widodo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia, as the world’s largest archipelagic state, faces complex maritime security threats, including piracy, illegal fishing, smuggling, and South China Sea tensions. These threats impact both national sovereignty and the economic and social welfare of coastal communities. Recognized as an archipelagic state under UNCLOS 1982, Indonesia has a strong legal foundation to claim inter-island waters under full sovereign jurisdiction. Using a qualitative approach and literature analysis, this study examines the role of the archipelagic state concept in designing adaptive maritime security policies. Findings indicate that this concept supports enhanced surveillance and law enforcement, although challenges in technology and coordination remain. Recommendations include strengthening technological capacity, inter-agency coordination, and international cooperation to bolster Indonesia’s maritime stability in the Indo-Pacific